Pharmacognostic evaluation and physico-chemical analysis of Ulmus wallichiana Planch. - Akhilesh; Bora, Kundan Singh (Journal of Applied Pharmaceutical Research, 2016)
The plant Ulmus wallichiana Planch. (Family: Ulmaceae) is found in Himalayan regions from Afghanistan to West Nepal. In India, it is found in Kumaun and Garhwal hills of Uttarakhand (India), locally known as Chamarmou. Bark of U. wallichiana is commonly used as Kumauni and Garhwali traditional healers for bone fracture of animals as well as human being. The current work was designed to establish the pharmacognostic parameters like macroscopic & microscopic characters, and physico-chemical analysis for U. wallichiana. WHO recommended methods and other standard procedures were employed for the establishment of pharmacognostic and physico-chemical parameters. Transverse section (TS) of the bark under the microscope showed periderm region showing cortex, mucilage canal, cork, phellogen and phelloderm. TS of the bark also showed secondary phloem region, medullary rays, stone cells and fibres. Longitudinal section showed medullary region, epidermal region and mucilage canal. Powder microscopy under the microscope showed calcium oxalate crystals, cork cells, phloem fibre, starch grains, stone cells and lignified phloem fibres. Physico-chemical analysis helps to identify pure plant material and detect adulteration. In the present study, total ash, water soluble ash, acid insoluble ash, sulphated ash and loss on drying were estimated to be 17%, 15%, 3.5%, 5%, 0.15% respectively. The findings of the present study could be useful in authentication of plant material and also in monograph preparation of U. wallichiana.